Regionalism from above: intergovernmental relations in Canadian metropolitan governance - Zack Taylor (Commonwealth Journal of Local Governance, 2022)
Robust metropolitan governance is increasingly viewed as necessary to address important economic, social and environmental problems. In this context, this article surveys recent developments in Canadian metropolitan governance. Canada was admired in the post-war period for the effectiveness of its two-tier and unitary metropolitan governments; however, few survive today as urbanisation patterns have become increasingly polycentric and intergovernmental relations more conflictual. Three models have emerged in Canada, sometimes in combination with one another: the multi-purpose regional intergovernmental organisation, the single-purpose metropolitan agency, and the provincial metropolitan policy overlay. Examples of each are discussed, with an emphasis on the interplay of horizontal (intermunicipal) and vertical (provincial–municipal) intergovernmental relations. Ultimately, provincial governments are by virtue of their constitutional authority and spending power the only actors capable of establishing and maintaining durable institutions and policies of metropolitan scope, and they have chosen to do so in Canada’s largest and most urbanised provinces.